GASTRONOMIC TOURISM MANAGEMENT REVITALIZER FACTOR OF THE TOURISM OFFER - MARIUS BOIŢĂ; ANDREI ANGHELINA; BOBY COSTI (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2014)
This work aims to present the gastronomic tourism, which is a new conception and form of tourism, dealt with separately from other forms of tourism, which combines features of cultural, thematically and durable tourism, aiming at meeting and educating tourists in traditional culinary arts, bringing benefits to the local people and maintaining various sectors of the economy. Gastronomic tourism consolidates, in this vision, as a key element in the diversification of the tourism supply and stimulation of the development of local regional, and national economy, with values of sustainability based on local and authentic products, in accordance with the current trends of cultural tourism consumption.